Risk Mitigation Production Process on Wood Working Line Using Fuzzy Logic Approach - Nazaruddin Nazaruddin; Winnie Septiani (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The wood working line process is the production process of wood raw materials formed according to the specified size to be used as part of the body of the piano. This study aims to design a priority mitigation model by identifying and measuring risks in the production process. The model is divided into two sub models, namely the risk measurement model and the risk mitigation model. The risk measurement model uses the Fuzzy Inference System (FIS) approach, the risk mitigation model uses the House of risk (HOR) approach. The results of risk measurement produce an output in the form of a Fuzzy Risk Priority Number. There are 7 potential risks, namely the risk of the inside of the plywood having space due to imperfect press, the risk of wind being trapped in the piano cabinet, the risk of imprecise wood drilling, the risk of cutting damage to the sides of the piano cabinet, the risk of the piano cabinet press not being up to standard, the risk of raw materials wood and glue don't mix, risk of peeling paint. There are 21 mitigation actions that are divided into each risk. HOR shows the value of the correlation between mitigation, sources of risk, ease of implementing risk. Keywords: Fuzzy Iference System; Fuzzy Risk Priority Number; House of Risk; Production Process. Risk Mitigation